Les actes des évêques d’Avranches, ca. 990-1253 : esquisse d’un premier bilan - Allen, R (Université de Caen, 2012)
While the acts of the other Norman dioceses, such as Bayeux, Evreux and Rouen, have been the subject of critical studies since the 1970s, those of the bishops of Avranches still remain among the most unknown documents of Norman historiography. If the history of the diocese of Avranches, the smallest as well as the least rich of the ecclesiastical province of Rouen, is well marked by patrimonial catastrophes (the collapse of the cathedral, the destruction of the archives of Saint-Lô), Nevertheless, there are enough documents to offer us not only a point of view on one of the most little-known episcopal chancelleries in Normandy, but also the possibility of better informing us on several historical, diplomatic facts.